PENGARUH BUDAYA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI MADRASAH ALIYAH - Andriansyah (UNISAN JURNAL, 2024)
This examination means to investigate the impact of authoritative culture and work inspiration on the presentation of Madrasah Aliyah Negeri 1 Metro educators. The strategy utilized in this exploration was an overview with a purposive testing method of 100 educators at 5 Madrasah Aliyah Negeri 1 Metro. Information was gathered through a survey utilizing a Likert scale. Information investigation was done utilizing numerous relapse tests. The examination results show that hierarchical culture and work inspiration affect the exhibition of Madrasah Aliyah Negeri 1 Metro instructors. A positive hierarchical culture can rouse educators to work better and team up with partners, while high work inspiration can spur instructors to accomplish hierarchical objectives and give quality Islamic training. For this situation, the administration of Madrasah Aliyah Negeri 1 Metro can work on the nature of Islamic schooling delivered by making a positive hierarchical culture and offering the right help and impetuses to increment instructor work inspiration. Great administration approaches can assist with further developing educator execution in giving quality Islamic schooling and shaping great understudy character. It is trusted that this examination can add to the improvement of Islamic training and the administration of instructive foundations in Indonesia